Increase in plasma resveratrol levels and in acid-resistant proteins in the acquired enamel pellicle after use of resveratrol-containing orodispersible tablets - Reis, Fernanda Navas; Câmara, João Victor Frazão; Dionizio, Aline; Araujo, Tamara Teodoro; Gomes da Silva, Natara Dias; Levy, Flávia Mauad; Ximenes, Valdecir Farias [UNESP]; Buzalaf, Marília Afonso Rabelo (Elsevier, 2024)
Objective: This study evaluated the effect of administration of trans-resveratrol-containing orodispersible tablets on the protein composition of the AEP and on blood plasma trans-resveratrol concentrations. Methods: Ten volunteers participated in two crossover double-blind phases. In each phase, after dental prophylaxis, they received a trans-resveratrol (15 mg) orodispersible tablet, or a placebo tablet (without actives). The AEP formed after 120 min was collected with electrode filter papers soaked in 3 % citric acid. Blood samples were collected 30, 45, 60 and 120 min after the use of the tablet. After protein extraction, AEP samples were analyzed by shotgun labelfree quantitative proteomics and plasma samples were analyzed by high-performance liquid chromatography (HPLC). Results: Eight hundred and two proteins were identified in the AEP. Among them, 336 and 213 were unique to the trans-resveratrol and control groups, respectively, while 253 were common to both groups. Proteins with important functions in the AEP had increased expression in the trans-resveratroltreated group, such as neutrophil defensins, S100 protein isoforms, lysozyme C, cystatin-D, mucin-7, alphaamylase, albumin, haptoglobin and statherin. Trans-resveratrol was detected in the plasma at all the times evaluated, with the peak at 30 min. Conclusions: The administration of trans-resveratrol in sublingual orodispersible tablets was effective both to increase the bioavailability of the polyphenol and the expression of antibacterial and acid-resistant proteins in the AEP, which might benefit oral and general health.
Keywords: Dental pellicle; Polyphenols; Proteins; Proteomics; Resveratrol; Tooth erosion